Post chemotherapy blood and bone marrow regenerative changes in childhood acute lymphoblastic leukemia a prospective study - Rashmi Kushwaha; Ashutosh Kumar; Kamal Aggrawal; Neha Nigam; Archana Kumar (Wolters Kluwer Medknow Publications, 2014)
Context: This study was done to assess the Serial peripheral blood and bone marrow changes in patients of Acute Lymphoblastic Leukemia on chemotherapy. Aims: To assess the therapy related serial bone marrow changes in patients of Acute Lymphoblastic Leukemia. Settings and Design: Prospective study, carried out in Lymphoma- Leukemia Lab, Department of Pathology, K.G.M.U from March 2011 to March 2012. A total of 60 cases were studied Materials and Methods: History, complete hemogram, bone marrow examination at pretherapy (Day-0), intratherapy (Day-14), and end of induction chemotherapy (Day-28) were done. Peripheral blood smears were evaluated at regular interval to assess clearance of blast cells. Statistical analysis used: The statistical analysis was done using SPSS (Statistical Package for Social Sciences) Version 15.0 statistical Analysis Software. The values were represented in Number (%) and Mean ± SD. The following Statistical formulas were used: Mean, standard deviation, Chi square test, Paired "t" test, Student 't' test, Level of significance P Results: Incidence of ALL-L1 (46.7%) and ALL-L2 (53.3%) was equal. ALL-L2 patients had poor survival.Day 0 (D-0) bone marrow was hypercellular with flooding of marrow by leukemic cells. High levels of tumor load at D'0' were associated with poor survival. 14 th day of Induction phase showed significant decrease in hemoglobin and TLC as compared to D '0' parameters. D28 showed marrow regeneration. Cellularity, Blast%, and Leukemic Index showed significant drop from day '0' to day 14 due to myelosupression, whereas regeneration reflected by increased cellularity as per day 28 marrow. Lymphocytosis (>20%) at end of induction chemotherapy had better survival and longer remission.Risk of mortality was directly proportional to blast clearance and was a major independent prognostic factor for achievement of complete remission. Conclusions: A bone marrow examination at the end of induction chemotherapy provides information whether patient has achieved remission with regeneration of cells or still has residual leukemia. If the patient is in remission, maintenance treatment is started and if not more intensive chemotherapy or bone marrow transplantation may be embarked upon.